2001
DOI: 10.1097/00002820-200106000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Living With Newly Diagnosed Breast Cancer—The Meaning of Existential Issues

Abstract: Menopausal symptoms are important concerns for breast cancer survivors, which may influence daily activities, physical comfort and sexual health. Incidence and severity ratings of menopausal symptoms contribute to our knowledge about menopause in women with cancer, but fail to fully describe the symptom experience. The purpose of this article is to broaden our understanding by describing variation in menopausal symptom distress and how women interpret and manage symptoms within the context of breast cancer. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 9 publications
1
45
0
3
Order By: Relevance
“…It has been indicated that cancer diagnosis and treatment cause the following psychological problems in women with breast cancer: anxiety, depression, anger, uncertainty about the future, fear of cancer recurrence, body image distortion, fear of losing female identity (Doumit et al, 2010;Denieffe and Gooney, 2011;Cebeci et al, 2012). In the literature, uncertainty and fear of recurrence are stated to be the most challenging experiences that women with breast cancer have in the process of diagnosis and treatment of the disease (Landmark et al, 2001;Doumit et al, 2010;Elmir et al, 2010). In our study too, women with breast cancer experienced problems such as uncertainty about the future and fear of cancer recurrence intensely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been indicated that cancer diagnosis and treatment cause the following psychological problems in women with breast cancer: anxiety, depression, anger, uncertainty about the future, fear of cancer recurrence, body image distortion, fear of losing female identity (Doumit et al, 2010;Denieffe and Gooney, 2011;Cebeci et al, 2012). In the literature, uncertainty and fear of recurrence are stated to be the most challenging experiences that women with breast cancer have in the process of diagnosis and treatment of the disease (Landmark et al, 2001;Doumit et al, 2010;Elmir et al, 2010). In our study too, women with breast cancer experienced problems such as uncertainty about the future and fear of cancer recurrence intensely.…”
Section: Discussionmentioning
confidence: 99%
“…After this experience, many changes occur in individuals. The meaning they attribute to life and priorities in their lives may change (Landmark et al, 2001). Tedeschi and Calhoun (2004) define this as post-traumatic growth.…”
Section: Discussionmentioning
confidence: 99%
“…For many women, shock is a common response to the diagnosis of breast cancer 6,23 and can petrify a lot of women, leading to turmoil, emotional chaos and the need to reorganise their lives to maintain control. 6,24 For many women this led to difficulties acknowledging the importance of the diagnosis 23 or failing to 'take much in' at the time of diagnosis. This was followed by the expectation that they were expected to cope with complex treatment cycles that were rapidly implemented.…”
Section: Discussionmentioning
confidence: 99%
“…47 A woman's ability to cope may be dependent on their psychological status prior to the diagnosis of breast cancer. This is thought to be the best indicator of how women cope with the illness trajectory 24 and may be dependent on a fighting spirit, aggressiveness, hostility and emotional anger 48 as indicated by some women in this study.…”
mentioning
confidence: 85%
“…The literature is fairly comprehensive regarding how women diagnosed with breast cancer cope with the initial diagnosis and the disease. Using qualitative methodologies research-ers have elicited the meanings that women subscribe to in coping with their disease (Jensen, Back-Petterson and Segesten, 2000;Landmark, Standmark and Wahl, 2001;Richer and Ezer, 2002). Studies point to the fact that women find meaning in their disease through at least eight categories.…”
Section: Introductionmentioning
confidence: 99%